Clinical profiles and trend analysis of newly diagnosed lung cancer in a tertiary care hospital of East China during 2011–2015 - Wang, Pingli; Zou, Jixia; Wu, Jingni; Zhang, Chengyan; Ma, Chengxi; Yu, Juan; Zhou, You; Li, Baizhou; Wang, Kai (Journal of Thoracic Disease; Vol 9, No 7 (July 31, 2017): Journal of Thoracic Disease, 2017)
Background: More than one-third of lung cancer worldwide occurring in China. However, the clinical profiles of lung cancer patients in the mainland of China are rarely reported and largely unknown. The objective of this study is to analyze the characteristics and time trends of newly diagnosed lung cancer cases during the past 5 years in East China. Methods: The data came from an academic tertiary care hospital of East China. Patients who were newly diagnosed as lung cancer from 2011 to 2015 were enrolled. All new cases got pathological supports by lung biopsy or surgery. Tumor staging was performed according to the seventh edition of the tumor node metastasis (TNM) classification of malignant tumors. The patients’ disease information was collected from the database of the hospital information system (HIS). Results: From 2011 to 2015, aggregately 5,779 patients, including 3,719 males and 2,060 females, were diagnosed as lung cancer. The major histologic subtypes of lung cancer were adenocarcinoma (ADC, 60.0%), squamous cell carcinoma (SCC, 25.6%), small cell lung cancer (SCLC, 8.5%), large cell carcinoma (0.6%), adenosquamous carcinoma (1%), other non-small cell carcinoma (1.6%) and unclassified or rare carcinoma (2.8%). ADC proportion of female was much higher than that of male. A higher proportion of advanced stage (stage IIIB, IV) of lung cancer existed in patients who were admitted to hospital due to respiratory or cancer related symptoms (RCRS) than those without RCRS. Smoking rate in male patients reached 80.2%, while it was only 2.7% in females. EGFR mutation existed in 66% of female and 37% of male patients with ADC. Conclusions: This study demonstrates the clinicopathologic characteristics of lung cancer patients from East China, including histologic composition, staging proportion, smoking prevalence and gene mutation status. During the past 5 years, the proportion of ADC has increased gradually whereas SCC decreased.